Drinking Levels and Profiles of Alcohol Addicted Rats Predict Response to Nalmefene - Foo, Jerome Clifford; Vengeliene, Valentina; Noori, Hamid Reza; Yamaguchi, Ikuhiro; Morita, Kenji; Nakamura, Toru; Yamamoto, Yoshiharu; Spanagel, Rainer (Frontiers in Pharmacology, 2019)
Background: Pharmacotherapeutic options supporting the treatment of alcohol dependence are recommended and available but underutilized, partly due to questions about efficacy. Nalmefene is recommended for reduction of alcohol consumption, but evidence about its effectiveness has been equivocal; identifying factors which predict response will help optimize treatment. Methods: The alcohol deprivation effect paradigm is a tightly controlled procedure comprising repeated deprivation and reintroduction phases, leading to increased preference for alcohol; reintroduction approximates relapse. Using a digital drinkometer system measuring high-resolution drinking behaviour, we examined the effects of nalmefene on relapse drinking behaviour in alcohol addicted rats. We also tested whether drinking behaviour in the relapse phase prior to nalmefene administration predicted treatment response. We further examined whether longitudinal drinking behaviour and locomotor activity predicted treatment response. Results: Our results showed that nalmefene (0.3mg/kg) reduced relapse-like consumption significantly (~20%) compared to vehicle on the first two days of alcohol reintroduction. Examining the first 6 hours of a preceded treatment-free relapse episode revealed drinking patterns clustering the rats into responders (reduction of >40%, n=17) and non-responders (reduction of <40%, n=7) to subsequent nalmefene treatment. During the first 6 hours of the preceding relapse phase, responders consumed more alcohol than non-responders; the amount of alcohol consumed during each drinking approach was larger but frequency of drinking did not differ. Longitudinal drinking behaviour and locomotor activity did not significantly predict response. Conclusions: Our results suggest that nalmefene reduces alcohol intake during a relapse-like situation but effectiveness can differ greatly at the individual level. However, who responds may be informed by examining drinking profiles and rats that show high drinking levels prior to treatment are more likely to respond to nalmefene.